2017
DOI: 10.24920/j1001-9294.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Crying Facies with Multiple Congenital Malformations: a Case Report

Abstract: SYMMETRIC crying facies (ACF) is characterizedby facial asymmetry only when crying. It may present as an exclusive symptom, or be concomitant with other congenital malformations and even some fatal birth defects. Clinically, ACF is featured by drooping of the intact corner of the mouth during crying, while the face appears symmetric at rest. The facial nerve function is symmetric, as determined by frowning, forehead wrinkling, eye closure, and nasolabial fold depth.When ACF alone is present, the cause is often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The procedure has led to a 4-month improvement in smile symmetry [ 32 ]. Permanent strategies for correcting ACF asymmetry consist of selective myectomy of the contralateral DAOM and selective neurectomy of the contralateral marginal mandibular branch of the facial nerve [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure has led to a 4-month improvement in smile symmetry [ 32 ]. Permanent strategies for correcting ACF asymmetry consist of selective myectomy of the contralateral DAOM and selective neurectomy of the contralateral marginal mandibular branch of the facial nerve [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies associate the occurrence of ACF syndrome with the deletion of 22q11.2 or 4p. Pasick et al found that 14% of the subjects (117/836) carrying 22q11.2 deletions exhibited ACF [18]. However, the genetic contributions of the genes located in 22q11.2 to symptoms of ACF remain unexplained.…”
Section: Potential Etiology Of Neonatal Asymmetric Crying Facies Syndromementioning
confidence: 99%
“…[ 6 ] Intrauterine viral infections, chromosomal aberrations, hereditary factors, or a defect located at the brainstem level can cause a defect in the depressor anguli oris muscle (DAOM) development, [ 2 ] one of the muscles that control the movements of the lower lip, on one side of the mouth. [ 4 , 7 ] Familial occurrence has been reported, and the mode of inheritance has been suggested as autosomal dominant inheritance with variable expressivity. [ 8 , 9 ] Some studies revealed that it is associated with chromosomal anomalies, such as 22q11.2 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…NACF has been suggested to be an indicator of coexisting anomalies, which can involve nearly all systems, such as the cardiac system, central nervous system, cervicofacial region, gastrointestinal and genitourinary system, respiratory system, musculoskeletal system, skin, and soft tissues, [ 2 , 9 ] the cervicofacial region and cardiovascular system being the most commonly involved. [ 4 ] Major cervicofacial malformations frequently occur on the same side as the DAOM hypoplasia. [ 9 ] In our case, the ear and left hand malformations were observed on the same side as the dysplasia of the DAOM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation